1555 Comparison of Face-To-Face Versus Online Delivery of a Preparatory Course for First Year Clinical Students. (12th October 2021) - Abdulhussein, D; Luo, R; Abou Sherif, S; Aseem, R; Pawa, N
Abstract: Aim: The coronavirus pandemic has had a huge impact on medical education, with increasing reliance on online delivery of teaching. Sound awareness of investigations available to clinicians is an essential skill, the foundations of which are built from the first clinical year. Our aim is to evaluate whether online teaching has the same efficacy as face-to-face teaching in the context of clinical investigations teaching. Method: We designed a case-based course using active learning methods (by means of audience participation tools) to prepare first year clinical students in interpreting key investigations (bedside, laboratory and imaging tests) with focus on surgical conditions. This course was delivered face-to-face in November 2019 and subsequently re-delivered via an online platform in November 2020. We utilised a pre- (PR) and post- (PS) confidence questionnaire and a 13-part mock single best answer examination. Results: 32 students attended the face-to-face course; 27 (84.3%) completed the PR and 21 (65.6%) completed the PS. There was a significant improvement in examination scores (56.9% to 71.7%, P < 0.01) and a significant improvement in one of the 6 confidence domains tested (interpreting abdominal radiographs, P < 0.001). 80 students attended the online course; 46 (57.5%) completed the PR and 40 (50%) completed the PS. There was a significant improvement in examination scores (58.8% to 73.2%, P < 0.001) and a significant improvement in two of the 6 confidence domains (interpreting laboratory tests and abdominal radiographs, P < 0.001 for both). Conclusions: Online teaching is as effective as face-to-face teaching in improving knowledge and confidence in clinical investigations for first clinical year students.